What Is the Cost of Privatization for Workers? - OLSSON, MARTIN; TÅG, JOACIM (Journal of Finance, 2025)
ABSTRACT Privatization of state‐owned enterprises is on the agenda across the globe. Using Swedish data covering two decades, we show that productivity gains and headcount reductions are associated with economic costs for incumbent workers. Workers experience income losses and higher unemployment, but half of the losses are covered by the social safety net. We also find small positive effects on entrepreneurship and cash holdings but no meaningful effects on other labor market, family, health, or household finance outcomes. Productivity improves when the CEO is replaced, and the gains outweigh workers' income declines by a factor of between two and six.